Age-related linear and nonlinear modelling of semen quality parameters in Miranda donkeys. Issue 1 (1st January 2021) - Martins-Bessa, Ana; Quaresma, Miguel; Leiva, Belén; Calado, Ana; Arando, Ander; Marín, Carmen; Navas, Francisco Javier
Abstract: In endangered donkey populations, reproductive performance is one the most important areas to study, provided its connection with conservation opportunities. Among reproductive traits, the knowledge on the evolution of seminal qualitative and quantitative parameters may achieve a particular relevance given its implication with improved or more efficient fertility and fecundation chances. The aim of the present study was to model the gonadosomatic index and the quantitative and qualitative seminal parameters along age in Miranda donkeys. Forty semen collections from 8 Miranda donkeys from 2.8 and 21.6 years of age, were fitted to eleven linear and nonlinear models. Cubic function modelling reported the best-fitting properties for almost all variables, except for sperm concentration (exponential model). Cubic model presented a slightly higher ability to capture interindividual variability than less parametrically complex models and more computationally complex models, such as exponential or logarithmic. Senility may course with and larger numbers of abnormal morphology spermatozoa, and also reduced sperm concentration and motility. Highlights: Testis reach mature size rapidly which may be ascribed to a breed factor. Age promotes ejaculate volume increase and concentration reduction. Reduced motility may ascribe to increased abnormal morphology spermatozoa. Major age-related changes are linked to testicular functions degeneration.